Komersialisasi Pupuk Organik Cair Berbasis Eco-Grow sebagai Upaya Pemberdayaan Ekonomi Komunitas Tasahi Kota Batam - Rusyda Nazhirah Yunus; Nursaima Harahap; Nursian Lubis (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2026)
Kitchen waste management remains a challenge in urban areas, including the city of Batam. Previous community service programs have resulted in improved knowledge and skills among the community in processing organic waste into Eco-Grow-based liquid organic fertilizer (POC). However, the program’s sustainability requires strengthening the economic aspect through product commercialization. Therefore, this follow-up activity aims to develop the production, packaging, and marketing of POC as a marketable product for the TASAHI community. The methods employed include production mentoring, branding and packaging training, and community-based marketing strategies. Results indicate that the community is capable of consistently producing POC and creating products in ready-to-sell packaging. The product has been marketed on a limited basis in the surrounding area at a price range of Rp15,000–Rp25,000 per liter. Additionally, there has been an increase in economic motivation and the formation of joint business initiatives at the community level. This initiative demonstrates that the commercialization of POC based on the Eco-Grow model not only contributes to waste reduction but also serves as a sustainable strategy for community economic empowerment.